Non-Surgical Treatment of Keratinocyte Skin Cancer - Jemec, Gregor B. E.; Kemeny, Lajos; Miech, Donald; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
Books mark the progress of Man since they were invented. Through them we are able to gain insight into the minds of our predecessors better than through any other medium. They describe how the delicate interplay between practice and ideal, which is better known as evolution, has brought forward the societies in which we now live. A book marks the synthesis of knowledge in a different way from individual papers. A certain maturity and volume of understanding and knowledge is necessary before the material is suitable for a book. The timing of the cognitive and analytical synt- sis represented by a book is therefore crucial; too soon and it is lost in speculation, too late and it is old news. Non-melanoma skin cancer is common; it causes morbidity, it causes a burden on society, and treatment has been traditionally almost exclusively surgical. Decades of medical science have however now brought forward a number of techniques which may help both the diagnosis and treatment of skin cancer without physically removing it, either alone or in combination in treatment programs tailored to the individual patients.
From Precursor to Cancer: Field Cancerization and the Opportunities for Therapy -- When Is a Skin Cancer a Cancer: The Histopathologist$1 (Bs View -- Epidemiology of Non-Melanoma Skin Cancer -- Genetics of Non-Melanoma Skin Cancers and Associated Familial Syndromes -- Environmental Risk Factors for Non-Melanoma Skin Cancers -- Accuracy in the Diagnosis of Non-Melanoma Skin Cancer -- Cure Rates Following Surgical Therapy $1 (BThe Golden Standard -- Pharmacological Therapy: An Introduction -- Systemic Chemotherapy of Non-Melanoma Skin Cancer -- Intralesional Agents to Manage Cutaneous Malignancy -- Topical Chemotherapy -- Immunotherapy: An Introduction -- Intralesional Interferon in the Treatment of Basal Cell Carcinoma -- Interleukin-2 for Nonmelanoma Skin Cancer -- Topical Imiquimod -- Photodynamic Therapy -- Critical Evidence-Based Review of Current Experience and Possible Future Developments of Topical PDT -- Electrochemotherapy in Treatment of Cutaneous Tumors -- Radiotherapy: At a Glance -- Prevention and Adjuvant Therapy -- Sunscreens -- Skin Cancer: Antioxidants and Diet -- Retinoids in the Management of Non-Melanoma Skin Cancer -- PDT for Cancer Prevention -- Dermabrasion, Laser Resurfacing, and Photorejuvenation for Prevention of Non-Melanoma Skin Cancer -- To Cut or Not, That Is the Question.s
Keywords: Medicine; Dermatology; Oncology; Medicine & Public Health; Dermatology; Oncology; Electronic books